Degradation of glass polymers due to successive exposure to acid rain and UV radiation (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Utilization of polymer products for outdoor applications is continuously increasing. So the stability of polymers against environmental degradation became top of interests for many researchers. The effect of environmental elements on the polymers stability has been studied, but individually. A solution against an environmental element may conflict with a solution against other element. Therefore current study aimed to clarify a sort of these conflicts. Polymethylmethacrylate (PMMA) films as example of glassy polymers are exposed to acid rains and Ultraviolet (UV) radiation in sequenced method for different time intervals. The effects on both structural and optical parameters are deduced from the measurements of Infrared spectra, X-ray diffraction charts, refractive indices and optical dispersion of samples before and after treatments. Chain scission is found to reduce the transparency of the samples. Acid rains are found to enhance the transparency of PMMA films by disordering chain fragments that are released by chain scission. Lot of experimental data are given in many coloured graphs.